Dillemas of Bad Loan Settlement of Village Credit Institution (Lembaga Perkreditan Desa) in The Covid-19 Pandemic Situation - I Nyoman Sujana; Leonito Ribeiro (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
This paper analyzes the dilemma of resolving bad loans of the Village Credit Institution (LPD) in the Covid19 Pandemic Era. The focus of the study is the problems faced by the Village Credit Institution (LPD) in resolving bad loans in Bali Province during the COVID-19 pandemic era. This study was conducted because LPDs in Bali experienced difficulties in securing credit even though the collaterals or guarantees were imposed with a mortgage as well as a Fiduciary during the Covid 19 period. As an analytical device on the legal issues studied, the author applied the theory of the welfare state with a statutory approach, a conceptual approach, a sociological approach, and a case approach. Based on the results of the study, it is found that the settlement of bad loans at the LPD is in a dilemma. “Internally“ the LPD noticed that the debtors, members of the traditional village, are taking refuge behind the Covid-19 pandemic situation, and denied their obligations. In the collateral cases, even though Mortgage Rights have been imposed with a fiduciary, settlement is about to be carried out, it turns out to be controlled by a third party who is a member of the Customary Village to execute loan settlement through the expropriation of the collateral by execution parate. This type of action is not allowed based on the principles of Balinese customary law paras, parosegilikseguluk, sarpanayasabayantaka. In this case, the LPD should go back to court. Meanwhile, “externally” the economic atmosphere affected by the Covid-19 pandemic has not yet recovered. Therefore, LPD faces a difficult choice between settling bad loans to recover the cash flow of a company, and taking measures to save credit by rescheduling, restructuring, and reconditioning. This rescue measure has become a heavy burden for LPDs to fulfill their obligations to credit customers.